Experimental study on the combustion sensitivity parameters and pre-combusted changes in functional groups of lignite coal dust - Cao, Weiguo; Cao, Wei; Peng, Yuhuai; Qiu, Shanshan; Miao, Nan; Pan, Feng (Powder technology, 2015)
Sensitivity parameters are critical for safety management and risk assessment of coal dust combustion process. In this paper, in order to evaluate the combustion sensitivity parameters and reveal the mechanism of lignite coal dust, 20L spherical explosion test apparatus and hot surface test apparatus were chosen to test the typical sensitivity parameters of lignite coal dust combustion. Results show that the limiting oxygen concentration of dust clouds (LOCC) was in the range of (13–14) %, and the minimum ignition temperature of dust layer (MITL) was in the range of (280–290) °C, respectively. The functional group variation law before combustion of lignite coal dust was tested by in-situ diffuse reflection Fourier transform infrared spectrometry (FTIR), and the proportions of functional groups in the lignite coal dust were analyzed from 30°C to 290°C. It is demonstrated that in coal dust combustion the key functional groups were CH3/CH2 and OH. [Display omitted] •We reveal the combustion sensitivity parameters of coal dust.•We analyzed the functional groups variation law of real-time before combustion.•We processed the functional groups by quantitative analysis methods.•The key functional groups were CH3/CH2 and OH in coal dust combustion.